Long-gap esophageal atresia: gastric transposition or esophageal lengthening with delayed primary anastomosis? A systematic review - Nasher, O; Hall, NJ; Mehta, R; El-Gohary, Y; Knight, M (Springer, 2024)
Purpose: This study aims to evaluate different surgical approaches to long-gap esophageal atresia (LGEA) with or without tracheoesophageal fistula (TEF) is unclear. Methods: A systematic literature review was done comparing gastric transposition versus esophageal lengthening with delayed primary anastomosis in infants with LGEA+/-TEF. The primary outcome was time to full oral feeds. Secondary outcomes were time to full enteric feeds, need for further surgery, growth, mortality, and postoperative adverse events. Results: No comparative studies were found. However, the literature was re-interrogated for non-comparative studies. Four hundred thirty-eight articles were identified and screened, and 18 met the inclusion criteria. All were case series. Forty-three infants underwent gastric transposition, and 106 had esophageal lengthening with delayed primary anastomosis. One study on gastric transposition reported time to full oral feeds, and one study in each group reported growth. Time to full enteric feeds was reported in one study in each group. 30% of infants had further surgery following gastric transposition, including hiatus hernia repair (5/43, 12%) and esophageal dilation (7/43, 16%). Following esophageal lengthening, 62/106 (58%) had anti-reflux surgery, 58/106 (55%) esophageal dilatation and 11/106 (10%) esophageal stricture resection. Anastomotic complications occurred in 13/43 (30%), gastrointestinal in 16/43 (37%), respiratory in 17/43 (40%), and nerve injury in 2/43 (5%) of the gastric transposition group. In the esophageal lengthening group, anastomotic complications occurred in 68/106 (64%), gastrointestinal in 62/106 (58%), respiratory in 6/106 (6%), and none sustained nerve injury. Each group had one death due to a cause not directly related to the surgical procedure. Conclusions: This systematic review highlights the morbidity associated with both surgical procedures and the variety in reporting outcomes.